Farmer’s Response to Agricultural Extension Activities in Suli Village Salahutu District of Central Maluku Regency - Gea, Dika Tika Krisnawati; P. N. Damanik, Inta; A. Far-Far, Risyart (Agrikan Jurnal Agribisnis Perikanan, 2023)
The results showed that the response of farmers to extension activities carried out by extension workers in Suli Village, Salahutu District, Central Maluku Regency was in the fairly good category. It is known that the visiting activities carried out by extension workers make good communication established with farmers, the preparation of extension materials which still lacks the impact of knowledge on farmers, the physical readiness of extension workers, the suitability of extension time that is not in accordance with the farmer's time where extension workers do not make promises to farmers in advance during extension activities, and the approach used by extension workers often uses an individual approach to farmers because extension agents find it easy to get responses from farmers in a short period of time. The availability of aids and teaching aids is greatly reduced, in the future it is hoped that there will be additional teaching aids and aids to help farmers understand and understand the material presented. There is a significant relationship between age, formal education level, and farming experience with the response given to extension activities, meaning that productive age will work better and maximally when compared to non-productive farmers, the higher the level of education a person will have the quality of skills increases in degree farming experience and superior understanding, thereby higher the level of experience and skills possessed by farmers in carrying out their activities in farming.